EKSPLORASI KONSEP MATEMATIKA DALAM SISTEM HUKUM WARIS ISLAM MASYARAKAT SEMUDUN - Pusfitasari, Ika; Hartoyo, Agung; Nursangaji, Asep (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe research was conducted because of the mathematical concepts related to human activities. One of them is a mathematical concept related to the distribution system of Islamic inheritance. The purpose of this research is to identify mathematical concepts related to the distribution of Islamic inheritance to the people in Semudun. The method of this research is descriptive method with five subjects moslem in Semudun. The results showed that the division of Islamic inheritance Semudun society contains a mathematical concept. There are the mathematical concepts contained in Islamic inheritance law; (1) The concept of the set is in the elements of the distribution system of inheritance law, which is a collection of heirs and a collection of heirs' assets; (2) The concept of integers is in the number of heirs, the heir portion number and the amount of heirs; (3) The concept of integer addition operations, integer subtraction operations, integer multiplication operations and integer division operations are in the process of calculating the inheritance division; (4) The concept of reducing fraction operations, fraction number division operations and fraction number multiplication operations that exist in the process of calculating the distribution of inheritance. Keywords : Mathematical Concepts, Islamic Inheritance Law, Community Semudun